In vivo analysis of the evolutionary conserved BTD-box domain of Sp1 and Btd during Drosophila development. - Blom-Dahl, D.; Córdoba, S.; Gabilondo, H.; Carr-Baena, P.; Díaz-Benjumea, F.J.; Estella, C. (Developmental Biology, 2020)
The Sp family of transcription factors plays important functions during development and disease. An evolutionary conserved role for some Sp family members is the control of limb development. The family is characterized by the presence of three C2H2-type zinc fingers and an adjacent 10 aa region with an unknown function called the Buttonhead (BTD) box. The presence of this BTD-box in all Sp family members identified from arthropods to vertebrates, suggests that it plays an essential role during development. However, despite its conservation, the in vivo function of the BTD-box has never been studied. In this work, we have generated specific BTD-box deletion alleles for the Drosophila Sp family members Sp1 and buttonhead (btd) using gene editing tools and analyzed its role during development. Unexpectedly, btd and Sp1 mutant alleles that lack the BTD-box are viable and have almost normal appendages. However, in a sensitized background the requirement of this domain to fully regulate some of Sp1 and Btd target genes is revealed. Furthermore, we have also identified a novel Sp1 role promoting leg vs antenna identity through the repression of spineless (ss) expression in the leg, a function that also depends on the Sp1 BTD-box.